2013
DOI: 10.1016/j.jphotobiol.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser therapy increases angiogenesis in a model of ischemic skin flap in rats mediated by VEGF, HIF-1α and MMP-2

Abstract: It is known that low level laser therapy is able to improve skin flap viability by increasing angiogenesis. However, the mechanism for new blood vessel formation is not completely understood. Here, we investigated the effects of 660 nm and 780 nm lasers at fluences of 30 and 40 J/cm2 on three important mediators activated during angiogenesis. Sixty male Wistar rats were used and randomly divided into five groups with twelve animals each. Groups were distributed as follows: skin flap surgery non-irradiated grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 28 publications
7
109
0
5
Order By: Relevance
“…36 Similarly, it has been shown that PBM (both 660 and 780 nm) improves the healing of skin flaps by enhancing the amount of new vessels formed in the tissue by modulating vascular endothelial growth factor (VEGF) secretion and HIF1a expression in a dose-dependent manner. 66 PBM has also been shown to rescue dendritic atrophy in the brain by upregulating brain-derived neurotrophic factor (BDNF) expression through induction of CREB. 67 Overall, the controlled expression and activity of transcriptional factors in response to laser-generated cellular stress are capable of coordinating a broad range of beneficial responses.…”
Section: Primary Indirect Events (Transducers)mentioning
confidence: 99%
“…36 Similarly, it has been shown that PBM (both 660 and 780 nm) improves the healing of skin flaps by enhancing the amount of new vessels formed in the tissue by modulating vascular endothelial growth factor (VEGF) secretion and HIF1a expression in a dose-dependent manner. 66 PBM has also been shown to rescue dendritic atrophy in the brain by upregulating brain-derived neurotrophic factor (BDNF) expression through induction of CREB. 67 Overall, the controlled expression and activity of transcriptional factors in response to laser-generated cellular stress are capable of coordinating a broad range of beneficial responses.…”
Section: Primary Indirect Events (Transducers)mentioning
confidence: 99%
“…22 It has also been shown that PBM events may also regulate vascular endothelial growth factor, enhancing the formation of new vessels and improving the healing of skin. 23 In summary, light treatments can lead to modulation of transcription factors capable of coordinating a wide range of beneficial responses in wound healing.…”
mentioning
confidence: 99%
“…Values found for the limb withdrawal threshold (in grams) for the pressure performed on the plantar surface (Plantar) and close to the incision (Local) in the pre-injury (Pre) times, 10 (10') and 60 (60') minutes of awakening. Discussion LLLT is a useful tool for the therapeutic field, aiming tissue repair (Bossini et al, 2012;Cury et al, 2013;Hussein, Alfars, Falih, & Hassan, 2011;Vasilenko et al, 2010), anti-inflammatory effects (Chen, Huang, Sharma, & Hamblin, 2011;Marcos et al, 2011) and analgesia (Chow et al, 2007;Chow, Johnson, Lopes-Martins, & Bjordal, 2009;Chow, Armati, Laakso, Bjordal, & Baxter, 2011;Eslamian, Shakouri, Ghojazadeh, Nobari, & Eftekharsadat, 2012;Rayegani et al, 2011;Yan et al, 2011). However, Aras et al (2010), in a review study, indicate a possible dubious effect of low power laser associated with anesthetics, since it can help or hinder the effects of anesthesia.…”
Section: Evaluation Of Nociceptionmentioning
confidence: 99%
“…Low level laser therapy (LLLT) has been widely used in clinical practice because it is not invasive, painless, easily administered (Bjordal et al, 2008), and has beneficial effects for the irradiated tissues, such as activation of microcirculation (Maegawa, Itoh, Hosokawa, Yaegashi, & Nishi, 2000), vasodilation production (Plass, Wieselthaler, Podesser, & Prusa, 2012) and neovascularization (Cury et al, 2013). LLLT modulates several biological processes, increasing mitochondrial respiration and ATP synthesis (Karu, 1999), changing enzymatic reactions by inhibiting the synthesis and release of prostaglandins (Marcos et al, 2011), besides producing analgesia via release of beta-endorphin (Meireles et al, 2012) and changes in nerve conduction (Chow, David, & Armati, 2007;Yan, Chow, & Armati, 2011).…”
Section: Introductionmentioning
confidence: 99%